Pemberatan Pidana Terhadap Orang Tua Yang Menjadi Pelaku Human Trafficking - Septian Rizkyansyah, H.R.; Adianto Mardijono (JOURNAL SAINS STUDENT RESEARCH, 2025)
The crime of human trafficking is also said to be a crime that is very complex and difficult to solve. In the case of human trafficking, this often involves not only one area of ​​life but several areas of life. The crime of human trafficking often occurs and it does not always occur within the territory of a country but also outside the territory of that country. However, children are a vulnerable group in discussions (child trafficking) that receive more attention. Violence against children is a violation of every child's rights, especially if the perpetrators of the violence are the child's parents. This is called domestic violence. The government has adopted regulations regarding the rights and protection of children in Indonesia, and implemented sanctions for violators of these regulations. The purpose of writing this newspaper is to find out criminal charges against parents who carry out human trafficking. This research was conducted using standard legal research methods. The normative legal method means, among other things, that this research uses an approach through primary sources relating to legal issues that need to be raised by combining them according to existing laws and regulations in Indonesia. The results of this study confirm that the sanctions applied to parents who commit acts of violence in the household are not only criminal sanctions but also civil sanctions, where parents as perpetrators, violators can be sued for compensation because they have harmed children as victims by not committing acts of violence. in the household. respect their rights.